Interventional Pain Physicians' Experiences of and Attitudes Toward Surgical Privileging. Issue 5 (1st August 2011) - Wright, Thelma B.; Enu, Ikay; Stansbury, Lynn G.; Roberts, Charles
Abstract : Background and Objectives: No consensus guidelines exist on surgical privilege credentialing for nonsurgeons. We queried a group of academic interventional pain physicians about their experiences acquiring such credentials after training, how this process reflected their training, and their current attitudes toward both processes. Methods: We designed an interactive, computer-based questionnaire and sent this electronically to the directors of all 93 accredited pain medicine subspecialty fellowship programs in the United States. The questionnaire included 17 items regarding interventional pain medicine training, procedures done, experience of credentialing for surgical privileges, and attitudes toward these processes, with 1 additional space for comments. Results: Of the 93 program directors, 46 (49.5%) responded to our questionnaire. Forty-one (89%) of the respondents were anesthesiologists, and 43 (93%) included some form of implantation procedure in their current practice. Most (83%) of the respondents did fewer than 25 implants per year. Experience doing implant procedures during training varied widely among respondents: 43% did fewer than 5 implant procedures during fellowship; 33.3% did at least 15. Most respondents did their own wound closures and did not feel that immediate surgical backup should be required for interventional pain procedures. Most respondents (78%) felt that pertinent surgical training should be mandatory before credentialing, but fewer than 20% reported having been required to have even a proctoring experience before credentialing. Conclusions: Experience doing implantation procedures during fellowship training and subsequent experience with hospital surgical credentialing seems to vary widely, even among interventional pain physicians associated with academic training programs.